Exploring the dust content of galactic haloes with Herschel III. NGC 891. Issue 1 (18th November 2020) - Yoon, J H; Martin, Crystal L; Veilleux, S; Meléndez, M; Mueller, T; Gordon, K D; Cecil, G; Bland-Hawthorn, J; Engelbracht, C
ABSTRACT: We present deep far-infrared observations of the nearby edge-on galaxy NGC 891 obtained with the Herschel Space Observatory and the Spitzer Space Telescope . The maps confirm the detection of thermal emission from the inner circumgalactic medium (halo) and spatially resolve a dusty superbubble and a dust spur (filament). The dust temperature of the halo component is lower than that of the disc but increases across a region of diameter ≈8.0 kpc extending at least 7.7 kpc vertically from one side of the disc, a region we call a superbubble because of its association with thermal X-ray emission and a minimum in the synchrotron scale height. This outflow is breaking through the thick disc and developing into a galactic wind, which is of particular interest because NGC 891 is not considered a starburst galaxy; the star formation rate surface density, 0.03 M⊙  yr −1 kpc −2, and gas fraction, just $10{{\ \rm per\ cent}}$ in the inner disc, indicate the threshold for wind formation is lower than previous work has suggested. We conclude that the star formation surface density is sufficient for superbubble blowout into the halo, but the cosmic ray electrons may play a critical role in determining whether this outflow develops into a fountain or escapes from the gravitational potential. The high dust-to-gas ratio in the dust spur suggests the material was pulled out of NGC 891 through the collision of a minihalo with the disc of NGC 891. We conclude that NGC 891 offers an example of both feedback and satellite interactions transporting dust into the halo of a typical galaxy.